PENINGKATAN KOMPETENSI GURU DALAM MENGOLAH NILAI BERBASIS MICROSOFT EXCEL MELALUI IN HOUSE TRAINING (IHT) DI SDN MURTAJIH 1 KABUPATEN PAMEKASAN - Sakrani (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2022)
This study aims to improve teacher competence in managing grades with Microsoft Excel through in-house training. Research for six months in odd semester 2021/2022. This study used the school action research method with 18 teachers as subjects at SDN Murtajih 1 Pademawu. This study used three cycles with each cycle for 2 months. In each cycle twice meetings are held with planning, action, observation and reflection activities. Data collection techniques using observation sheets. Data analysis using descriptive analysis. The results of the study prove that there is an increase in teacher competence in processing grades using Microsoft Excel through in-house training. The results of the cycle prove that in the first cycle the teacher's ability to process grades is quite good with an acquisition of 66%. Then in cycle II the teacher's ability increased to be good with an acquisition of 80%. While in cycle III it increased to very good with a gain of 92%. Thus it can be concluded that in-house training activities have a positive impact on improving teacher quality so that follow-up activities are needed so that they run continuously.